Suppression of Insulin Secretion by Ghrelin and The Deterioration of Glucose Tolerance in Healthy Children - NoorAldeen, Zena E.; EL-Yassin, Hedef D.; Al Naddawi, Mahjoob N.l (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Ghrelin, identified as an endogenous ligand for the growth hormone secretagogue receptor, functions as a somatotrophic and orexigenic signal from the stomach. The secretion of ghrelin increases under conditions of negative energy balance, such as starvation, cachexia, and anorexia nervosa, whereas its expression decreases under conditions of positive energy-balance such as feeding, hyperglycemia, and obesity. In addition to having a powerful effect on the secretion of growth hormone, ghrelin stimulates food intake and transduces signals to hypothalamic regulatory nuclei that control energy homeostasis. Thus, it is interesting to note that the stomach may play an important role in not only digestion but also as a pituitary growth hormone release and central feeding regulation. Objective: The goal of this study was to test the hypothesis that circulating ghrelin suppresses insulin secretion in healthy children. Subjects and methods: Enzyne-Linked immunosorbent assay method was used to assay Ghrelin and Insulin. By taking blood sample from 40 obese children, 11 overweight children and 29 normal weight healthy children their age (5-11) years. Results: the mean concentration of Ghrelin was significantly lower in obese and overweight children than in controls ( P < 0.000 ) . The mean concentration of Insulin was significantly higher in obese and overweight children than in controls ( P < 0.007 ). Negative correlations was obtained between Ghrelin and BMI, also negative correlation between Ghrelin and Insulin was obtained. Conclusions: This study showed that ghrelin reduces insulin secretion and glucose disappearance in healthy children. This findings raise the possibility that endogenous ghrelin has a role in physiologic insulin secretion, and that its antagonist may improve β-cell function.